Lazer e camadas populares: reflexões a partir da obra de Edward Palmer Thompson - Victor Andrade De Melo (Universidade Federal do Rio Grande do Sul, 2001)
This article has for purpose to discuss some contribution of Edward Palmer Thompson thought as theoretical inspiration to studies dedicated to research thepeculiarities ofworking classes leisure activities. To reach the goal, it voas analyzed the principal Thompson books, mainly his masterpiece-. "The making ofworking class". I would like that this article can contribute to others researchers that are interested in differentpoint ofview of leisure in a stratified society, aswell to collaborate to new comprebensions in Leisure Theory.